Nanobubble-assisted scaling inhibition in membrane distillation for the treatment of high-salinity brine. (1st February 2022) - Farid, Muhammad Usman; Kharraz, Jehad A.; Lee, Cheng-Hao; Fang, James Kar-Hei; St-Hilaire, Sophie; An, Alicia Kyoungjin
Highlights: Simple and chemical-free approach for scaling inhibition in MD. Air NBs have neutral buoyancy, small size (128.81 nm), high concentration (7.8 × 10 7 bubbles mL −1 ), and negative surface charge. A one-time addition of air NBs in high-salinity feed reduced scaling and prolonged the effective MD operating time. The use of NBs resulted in significantly less salts deposition and prevented the occurrence of pore wetting. Scaling inhibition mechanisms include NB-induced surface shear forces, and NBs-counterions electrostatic attractions. Abstract: In this study, we report the use of nanobubbles (NBs) as a simple and facile approach to effectively delay scaling in membrane distillation (MD) during the treatment of highly saline feed (100 g L −1 ). Unlike conventional gas bubbling in MD for improving the hydrodynamic flow conditions in the feed channel, here we generated air NBs with an average size of 128.81 nm in the feed stream and examined their impact on membrane scaling inhibition during MD operation. Due to their small size, neutral buoyancy, and negative surface charge, NBs remain in suspension for a longer time (14 days), providing homogenous mixing throughout the entire feed water. The MD performance results revealed that severe membrane scaling happened during the DCMD treatment of high salinity brine in the absence of nanobubbles, which dramatically reduced the distillate flux to zero after 13 h. A one-time addition of air NBs in the saline feed significantly reduced salt precipitation and crystal deposition on the PVDF membrane surface, delayed the occurrence of flux decline, prevented membrane wetting, thereby prolonging the effective MD operating time. With similar feed concentration and operating conditions, only 63% flux decline after 98 h operation was recorded in nanobubble-assisted MD. Two key explanations were suggested for the delayed membrane scaling upon addition of air NBs in the MD feed: (1) NB-induced turbulent flow in the feed channel that increases the surface shear forces at the membrane surface, alleviating both temperature and concentration polarization effect, (2) electrostatic attractions of the counterions to the negatively charged NBs, which reduces the availability of these ions in the bulk feed for scale formation. Graphical abstract: Image, graphical abstract